1993
DOI: 10.1080/10408399309527643
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein concentrates and isolates: Processing and functional properties

Abstract: Substantial progress has been made in understanding the basic chemical and structural properties of the principal whey proteins, that is, beta-lactoglobulin (beta-Lg), alpha-lactalbumin (alpha-La), bovine serum albumin (BSA), and immunoglobulin (Ig). This knowledge has been acquired in terms of: (1) procedures for isolation, purification, and characterization of the individual whey proteins in buffer solutions; and (2) whey fractionation technologies for manufacturing whey protein concentrates (WPC) with impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
294
2
33

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(362 citation statements)
references
References 145 publications
8
294
2
33
Order By: Relevance
“…Calvo and De la Hoz [2] suggested that dimethyl disulfide may be formed from the release of the activated sulfydryl groups of β-lactoglobulin during the heat denaturation of whey proteins. Sulfur compounds often have very low sensory thresholds, and thus they contribute to the flavor or off-flavor of many food products, even at very low concentrations [14].…”
Section: Resultsmentioning
confidence: 99%
“…Calvo and De la Hoz [2] suggested that dimethyl disulfide may be formed from the release of the activated sulfydryl groups of β-lactoglobulin during the heat denaturation of whey proteins. Sulfur compounds often have very low sensory thresholds, and thus they contribute to the flavor or off-flavor of many food products, even at very low concentrations [14].…”
Section: Resultsmentioning
confidence: 99%
“…The physico-chemical and functional properties of whey proteins have been extensively reviewed [19,24] and would appear to satisfy the requirements of an encapsulating agent. Microencapsulating properties of whey proteins have been investigated and reported in recent years [18,29].…”
Section: Introductionmentioning
confidence: 99%
“…Whey proteins are extensively used as functional ingredients in food systems [24]. The physico-chemical and functional properties of whey proteins have been extensively reviewed [19,24] and would appear to satisfy the requirements of an encapsulating agent.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the processes employed to obtain whey protein isolate (WPI) are microfiltration, ultrafiltration, spray drying, ion exchange and other elite proprietary processes that are proprietary. (12) The processes employed in manufacturing WPI significantly affect 1) which bioactive proteins are isolated and preserved and 2) the quality of these proteins (ie, the degree of denaturation). WPI are high in bioactive compounds which have broad therapeutic effects.…”
Section: Non-denatured Whey Protein Isolatesmentioning
confidence: 99%